Asteroids IV - Michel, Patrick, 1970-; DeMeo, Francesca E.; Bottke, William F. (William Frederick), 1966- (Book collections on Project MUSE., 2015)
"More than forty chapters detail our current astronomical, compositional, geological, and geophysical knowledge of asteroids, as well as their unique physical processes and interrelationships with comets and meteorites"--Provided by publisher.